Concepts and experiences with demand driven advisory services: Review of recent literature with examples from Tanzania - Esbern Friis-Hansen (Danish Institute for International Studies (DIIS), 2004)
The current institutional framework for agricultural services in East and Southern Africa was designed for a state-sponsored supply-driven approach. These institutions demand large field staff levels and are associated with high costs often financed by World Bank loans. These institutions are moreover ill-suited to respond to the demands from clients that are now emerging through development interventions and policies. Farmers are marginally involved with planning the content and means of service provision. Top-down approaches also fail to target agricultural services to women and vulnerable groups. Demand-driven advisory services have evolved over recent years and involve changing the role of extension agents from advisors to facilitators; increasing control by farmers through cost sharing; increasing the use of contracted services; and emphasizing knowledge provision rather then narrow technical advice. The DIIS Working Paper discusses four conceptual aspects of this changing approach to extension. First the working paper discusses the shift in international thinking about extension. This includes an analysis of the key principles of the conventional Training and Visit Extension methodology and the new emerging Client-driven Advisory Services model. Secondly, the management implications of the shift in paradigm are discussed, emphasizing the change in relationship between farmers and external actors. Thirdly, the working paper is concerned with the approach to farmer learning. The fourth aspect discussed is the technology development processes associated with the extension models. The working paper finally reviews a range of experiences in Tanzania with new forms of extension. – – Mange offentlige institutioner inden for landbrugssektoren i Afrika blev grundlagt medens landbrugspolitikken stadig var domineret af en udbudsdrevet moderniseringstilgang, finansieret af store lån fra Verdensbanken og med mange ansatte og store omkostninger. Bønderne havde kun ringe indflydelse på indholdet og tilgangen til udvikling af landbrugsteknologi og rådgivning. Landbrugskonsulenttjenesten er i mange afrikanske lande snævert fokuseret på produktion og har ikke magtet at gøre deres rådgivning relevant for kvinder eller fattige og udsatte grupper. Reformer af den offentlige sektor i forbindelse med 1990ernes strukturtilpasningsprogrammer og reducerede statsbudgetter har generelt svækket disse landbrugsinstitutioner. En efterspørgselsdrevet tilgang til landbrugskonsulenttjeneste er blevet udviklet gennem de seneste år og er blevet debatteret mellem internationale donorer og nationale aktører. Denne tilgang involverer en ændret rolle for landbrugskonsulenten fra rådgiver til facilitator, at bønderne får øget kontrol over indhold og form, og mere vægt på at stimulere bredere viden blandt bønderne frem for snæver teknisk rådgivning. På basis af en litteraturgennemgang diskuterer DIIS arbejdspapiret fire aspekter af den ændrede tilgang til konsulenttjenesten. Først analyseres de vigtigste begreber i T&V-tilgangen og den nye efterspørgsels-drevne tilgang til landbrugskonsulenttjenesten. Derefter diskuteres ledelsesmæssige implikationer af skiftet i tilgang, med vægt på magtforholdet mellem bønder og eksterne aktører. Det tredje aspekt vedrører pædagogisk metode og tilgang til indlæring, der i stigende omfang anvender ikke-formelle voksenundervisningsprincipper. Det fjerde aspekt der diskuteres, er den stigende inddragelse af bønder i udvikling og tilpasning af landbrugsteknologi. Sidst i arbejdspapiret findes en gennemgang af hidtidige erfaringer fra Tanzania med øget bonde-styring og efterspørgsels-drevet landbrugskonsulenttjeneste.
Keywords: 330; Landwirtschaftliche Beratung; Tansania